Utilization patterns and characteristics of users of biologic anti‐inflammatory agents in a large, US commercially insured population - Aaron B. Mendelsohn; Young Hee Nam; James Marshall; Cara L. McDermott; Bharati Kochar; Michael D. Kappelman; Jeffrey S. Brown; Catherine M. Lockhart (Wiley, 2021)
Abstract We report utilization patterns and characteristics of patients treated with biologic anti‐inflammatory agents in a large commercially insured patient population in the United States. We identified adult (age ≥18 years) patients receiving biologic anti‐inflammatory agents between 1 January 2012 and 31 March 2019 across the five Research Partners in the Biologic and Biosimilars Collective Intelligence Consortium's Distributed Research Network. We examined the number of incident use episodes for each biologic, as well as patient demographic and clinical characteristics. Curated data and analytic tools from the Food and Drug Administration's Sentinel System were used to perform the analyses. We identified 90,360 incident episodes of tumor necrosis factor‐alpha inhibitors (TNFi) and 70,506 incident episodes of non‐TNFi medications. Adalimumab was the most common TNFi drug (47% of all TNFi episodes) and showed a steady increase in utilization during the study period compared to other TNFi agents. Rituximab was the most commonly initiated non‐TNFi medication (44% of non‐TNFi episodes). Other non‐TNFi agents, namely, ustekinumab, vedolizumab, and secukinumab, demonstrated notable increases in utilization over time. Biosimilar use was limited; we observed 653 incident episodes for infliximab‐dyyb and 39 incident episodes for infliximab‐abda. As more biologics enter the market, greater variation in the use of biologics with similar indications and between biologic originators and biosimilars is anticipated. Because information on efficacy and safety at the time of drug approval is limited, post‐marketing surveillance and research is needed to monitor medication safety and evaluate effectiveness between biologic drugs using real‐world data.